2015
DOI: 10.1016/j.jaci.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial to evaluate azithromycin's effects on serum and upper airway IL-8 levels and recurrent wheezing in infants with respiratory syncytial virus bronchiolitis

Abstract: Background Respiratory syncytial virus (RSV) bronchiolitis in infancy is a major risk factor for recurrent wheezing and asthma. As azithromycin attenuated neutrophilic airway inflammation in a murine viral bronchiolitis model, demonstration of similar effects in humans may provide a strategy for the prevention of post-bronchiolitis recurrent wheezing. Objectives To investigate whether azithromycin treatment during RSV bronchiolitis reduces serum and nasal lavage IL-8 levels and the occurrence of post-bronchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
127
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(136 citation statements)
references
References 53 publications
2
127
2
4
Order By: Relevance
“…Viral infections are associated with neutrophilic airway inflammation and increased expression of the dominant neutrophil chemoattractant IL - 8, 23,24 and azithromycin has recently been demonstrated to reduce IL-8 levels in nasal secretions during respiratory syncytial virus bronchiolitis. 25 However, although polymorphisms in the IL-8 gene also have been shown to modulate IL-8 production, 11 we did not observe a significant interaction between reduced risk of progressing to severe LRTI and the IL-8 rs4073 polymorphism.…”
Section: Discussioncontrasting
confidence: 61%
“…Viral infections are associated with neutrophilic airway inflammation and increased expression of the dominant neutrophil chemoattractant IL - 8, 23,24 and azithromycin has recently been demonstrated to reduce IL-8 levels in nasal secretions during respiratory syncytial virus bronchiolitis. 25 However, although polymorphisms in the IL-8 gene also have been shown to modulate IL-8 production, 11 we did not observe a significant interaction between reduced risk of progressing to severe LRTI and the IL-8 rs4073 polymorphism.…”
Section: Discussioncontrasting
confidence: 61%
“…1,2 We recently reported that, in a proof-of-concept randomized trial (the Azithromycin to Prevent Wheezing following RSV Bronchiolitis trial), azithromycin (AZM) therapy during RSV bronchiolitis reduced the probability of developing RW during the subsequent year by approximately 50%. 3 AZM was chosen because it is capable of targeting neutrophilic airway inflammation 4 and based on our results in a mouse model of viral bronchiolitis. 5 In infants hospitalized with RSV bronchiolitis, we demonstrated anti-inflammatory effects of AZM 3 reflected by reduced nasal lavage levels of IL-8, a marker of neutrophilic airway inflammation.…”
mentioning
confidence: 99%
“…3 AZM was chosen because it is capable of targeting neutrophilic airway inflammation 4 and based on our results in a mouse model of viral bronchiolitis. 5 In infants hospitalized with RSV bronchiolitis, we demonstrated anti-inflammatory effects of AZM 3 reflected by reduced nasal lavage levels of IL-8, a marker of neutrophilic airway inflammation. However, the mechanism of AZM's anti-inflammatory effects may have reflected direct effects on the immune response, or an indirect effect through antibacterial actions of AZM leading to alteration in bacteria abundance and a reduction in neutrophilic inflammation.…”
mentioning
confidence: 99%
“…ECP is a specific marker of eosinophils (Ursaciuc et al, 2010;Shah et al, 2012;Beigelman, 2014;Smith et al, 2015), which is mainly activated and released by eosinophils and causes neurotoxicity and cytotoxicity. In addition, ECP induces release of histamine by mast cells, causing airway hyperresponsiveness, resulting in bronchial asthma attack (Reed et al, 2007;Choi et al, 2010;Chua et al, 2010;Ursaciuc et al, 2010;Wei et al, 2010;Braga et al, 2011;Olive et al, 2011).…”
Section: Discussionmentioning
confidence: 99%